2006
DOI: 10.1080/09540100600918169
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intestinal mucosal immunity by dietary polyunsaturated fatty acids in chickens

Abstract: This study was undertaken to investigate the effects of dietary polyunsaturated fatty acids (PUFA) on intestinal immune responses and cytokines secretions in chickens at nutritionimmunity level. The proportion of CD3' CD8 ' lymphocytes of intestinal mucosa in CO group was higher on d 21 than that in FO (p B/ 0.01) and PO (p B/ 0.05) group. The proportion of CD3' CD4 ' lymphocytes of FO group was greatly significantly higher on d 21, relative to PO or CO group. The FO treatment enhanced the sIgA concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The production of sIgA is of major importance to the function of the mucosal immune systems of broiler. Like the other type of immunoglobulins, the mucosal sIgA concentration of poultry is affected by the ratio of n-3 to n-6 PUFA through eicosanoid mediated effect (Miura et al, 1998;Yang and Guo, 2006). In accordance to Spolaore et al (2006) who have shown that alga as a part of animal feed could improve the immune response, and also concomitant to Yang and Guo (2006), our results suggest that increased levels of Chlorella sp.…”
Section: Mucosal Siga Concentrationsupporting
confidence: 81%
“…The production of sIgA is of major importance to the function of the mucosal immune systems of broiler. Like the other type of immunoglobulins, the mucosal sIgA concentration of poultry is affected by the ratio of n-3 to n-6 PUFA through eicosanoid mediated effect (Miura et al, 1998;Yang and Guo, 2006). In accordance to Spolaore et al (2006) who have shown that alga as a part of animal feed could improve the immune response, and also concomitant to Yang and Guo (2006), our results suggest that increased levels of Chlorella sp.…”
Section: Mucosal Siga Concentrationsupporting
confidence: 81%
“…The lymphocyte subpopulations (CD3 þ , CD4 þ and CD8 þ T cells) in the lymphocyte cell suspension prepared above were determined using the flow cytometric method (Holt et al, 2010;Yang and Guo, 2006). Viable cell counts were determined by trypan blue exclusion and the cell concentrations were adjusted to 2 Â 10 6 viable cells/ml.…”
Section: Determination Of Intestinal Lymphocyte Subpopulationsmentioning
confidence: 99%
“…Briefly, the mesentery-, fat-and blood vessels-free ileum segments were cut into o0.5 cm pieces, washed with PBS containing 100 IU/ml penicillin and 100 μg/ml streptomycin and incubated at 37°C with 20 ml digestive culture medium (Yang and Guo, 2006) for 90 min. The suspensions were filtered through 200 mm nylon cloth and the filtrates were centrifuged with an Allegra™ 64R Centrifuge (Beckman Coulter, Inc., CA) at 500g for 10 min.…”
Section: Determination Of Intestinal Lymphocyte Subpopulationsmentioning
confidence: 99%
“…However, given the inconsistent results of several studies, this concern may or may not be justified. Some studies show no effect (Puthpongsiriporn and Scheideler, , Bautista‐Ortega et al., ), some show a detrimental effect (Pappas et al., ; Al‐Khalifa et al., ), and some show an improvement (Wang et al., ; Yang and Guo, ; Enting et al., ). In our study, the inclusion level of 3.0% was probably too high, thereby provoking negative effects.…”
Section: Discussionmentioning
confidence: 99%